Strengthening Msme Branding Competencies Through Social Media-Based Problem Based Learning (Pbl) in the Context Of Student Business Management - Winda Widya Dini; Feriandy; Deni Indra Purnama Koto (Indonesian Journal of Business Analytics, 2026)
This study aims to analyze the effectiveness of implementing the Problem Based Learning (PBL) method assisted by social media in improving students’ MSME branding abilities from a business management perspective. The background of this study is based on the still limited practical abilities of students in implementing digital branding strategies relevant to business needs. The research method used is Classroom Action Research (CAR), conducted in two cycles, including the stages of planning, implementation, observation, and reflection. The research subjects were Management Study Program students taking the Social Media Technology course. Data collection techniques were carried out through observation, performance assessment, documentation, and questionnaires, while data analysis used qualitative and quantitative approaches. The results of the study indicate a significant improvement in students’ abilities in the aspects of branding strategy planning, content creativity, and MSME social media management, with the average score increasing from 66.7 in Cycle I to 83.3 in Cycle II. In addition, there was an increase in student participation, collaboration, and active involvement in the learning process. These findings indicate that the integration of PBL with social media is able to create contextual, applicable, and experience-based learning that is relevant to modern business management practices, particularly in digital marketing and MSME development.